PENGGUNAAN DAN NIAT PERILAKU MENGGUNAKAN SISTEM INFORMASI DESA DI ANTARA PEMERINTAH KALURAHAN MURTIGADING DENGAN PENDEKATAN MODEL UTAUT-2 - Dadang Heksaputra; Ragil Satria Wicaksana; Dhina Puspasari Wijaya; Vega Lavenia; Akbar Nur Rizqi (Universitas Alma Ata, 2024)
The village information system has experienced significant growth, but research focusing on user adoption behavior in the Kalurahan Murtigading government area remains limited. Additionally, most studies use a single theoretical framework to explore this behavior. Addressing this gap, this study applies the UTAUT-2 framework to analyze the key factors influencing behavioral intention to use the village information system among the Kalurahan Murtigading government, with the addition of perceived security and epistemic value as other influencing factors. The study employs a survey approach with a cross-sectional design, and the proposed conceptual model was tested using partial least squares-structural equation modeling (PLS-SEM) analysis on 38 samples, with no issues of non-response bias (NRB) and common method bias (CMB). The results indicate that the UTAUT-2 constructs, along with the additional factors, significantly influence behavioral intention, with social influence, effort expectancy, and epistemic value being the top three factors affecting behavioral intention. These findings can also assist stakeholders in developing effective strategies to encourage more individuals, especially in the Kalurahan Murtigading government area, to adopt the village information system.